Social Support and Work Engagement Among Secondary School Teachers in Hong Kong (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—This study investigated work engagement and social support for 386 secondary school teachers in Hong Kong. It was driven by highly documented issues regarding their below-optimal physical and psychological well-being, which degrades personal well-being as well as the quality of education. Not only was it the aim of this research to quantitatively quantify these two variables, but also to establish a proactive approach to establish how to cultivate positive psychological strengths to maximise engagement. The goal was to provide a pathway for improving the quality of life and overall professional performance of teachers, creating a circle of virtuousness to the advantage of both students and teachers. Data was collected via well-designed web questionnaires and were processed using a stringent statistical approach. The key results offered a mixed and eye-opening picture: while a promising 63.7% of teachers demonstrated social support scores above the median, a much lower but disturbing percentage (43.3%) reflected high work engagement. This disconnection between support systems and engagement suggests that support systems per se are in place, yet perhaps not being maximally applied or to optimal targets. Most notably, the researchers have identified a moderate positive correlation, statistically confirming that greater perceived social support is associated in concrete terms with enhanced work engagement. This turns the finding from anecdotal observation to empirical fact. The relevance of the study transcends mere academic diagnosis to providing actionable intelligence for principals and policymakers alike. It emphasizes the sheer necessity to intentionally strengthen structural and affective support systems and, simultaneously, try to remove the underlying psychological health barriers facing teachers. These findings are highly relevant to teacher training colleges in course design, for school administration in setting supportive working cultures, and to the broader public that relies on a secure, motivated teaching profession.